Where art thou louse? A snapshot of attachment location preferences in salmon lice on Atlantic salmon hosts in sea cages - Bui, Samantha (Journal of fish diseases, 2020)
© 2020 The Authors. Journal of Fish Diseases published by John Wiley & Sons Ltd.